The interaction between family law, succession law and private international law : adapting to change - Scherpe, Jens M., 1971-; Bargelli, Elena (Cambridge : Intersentia, 2021)
There can be no doubt that both substantive family and succession law engage in significant interaction with private international law, and, in particular, the European Union instruments in the field. While it is to be expected that substantive law heavily influences private international law instruments, it is increasingly evident that this influence can also be exerted in the reverse direction. Given that the European Union has no legislative competence in the fields of family and succession law beyond cross-border issues, this influence is indirect and, as a consequence of this indirect nature, difficult to trace. This book brings together a range of views on the reciprocal influences of substantive and private international law in the fields of family and succession law. It outlines some key elements of this interplay in selected jurisdictions and provides a basis for discussion and future work on the reciprocal influences of domestic and European law. It is essential that the choices for and within certain European instruments are made consciously and knowingly. This book therefore aims to raise awareness that these reciprocal influences exist, to stimulate academic debate and to facilitate a more open debate between European institutions and national stakeholders. With contributions by Elena Bargelli (University of Pisa, Italy), Anne Barlow (University of Exeter, England, United Kingdom), Elena D'Alessandro (University of Turin, Italy), Elise Goossens (KU Leuven; Vrije Universiteit Brussel; University of Antwerp, Belgium), Nigel Lowe (Cardiff University, Wales, United Kingdom), Robert Magnus (University of Bayreuth, Germany), Maire Ni Shuilleabhain (University College Dublin, Ireland), Walter Pintens (KU Leuven, Belgium; Saarland University, Germany), Pablo Quinza Redondo (University of Valencia, Spain), Lukas Rass-Masson (University of Toulouse, France), Anne Sanders (University of Bielefeld, Germany), Jens M. Scherpe (University of Cambridge, England, United Kingdom; University of Hong Kong; University of Aalborg, Denmark; University of the Western Cape, South Africa), Wendy Schrama (Utrecht University, The Netherlands), Denise Wiedemann (Max Planck Institute for Comparative and International Private Law, Hamburg, Germany).
Title from publisher's bibliographic system (viewed on 28 May 2021).
Keywords: Domestic relations -- Europe; Law of succession -- Europe